1983
DOI: 10.1070/qe1983v013n09abeh004675
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion anomalies of tuning characteristics and spectrum of an optical parametric oscillator

Abstract: Recently, it has been shown that if we consider the higher derivative correction, the viscosity bound conjectured to be η/s = 1/4π is violated and so is the causality. In this paper, we consider medium effect and the higher derivative correction simultaneously by adding charge and Gauss-Bonnet terms. We find that the viscosity bound violation is not changed by the charge. However, we find that two effects together create another instability for large momentum regime. We argue the presence of tachyonic modes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…57b in comparison to Fig. 57a, it can be concluded that in the spectral range where the spectral gain bandwidth is determined by higher-order dispersion terms, the effect of the gain coefficient, Γ , is rather weak [111,142]. Figs.…”
Section: Ultrabroadband Wlc Generation In Bibomentioning
confidence: 96%
See 2 more Smart Citations
“…57b in comparison to Fig. 57a, it can be concluded that in the spectral range where the spectral gain bandwidth is determined by higher-order dispersion terms, the effect of the gain coefficient, Γ , is rather weak [111,142]. Figs.…”
Section: Ultrabroadband Wlc Generation In Bibomentioning
confidence: 96%
“…It is clear that for collinear type-I interaction, the third-order term (10) also vanishes near degeneracy, and this makes it necessary to consider the fourth-order term [111]. From our consideration, this term is given by Eq.…”
Section: Spectral Acceptance and Parametric Gain Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an OP-GaAs optical parametric oscillator (OPO) of ns pulse duration was built and produced tunable output from 2-11 µm [5]. We recently demonstrated optical parametric generation (OPG) in OP-GaAs that produced an ultrabroad infrared continuum [6].Extremely wide tuning bandwidths for parametric processes are associated with the zero-GVD wavelength [7]. For an interaction where d 2 k/dω 2 = 0 at the degenerate signal-idler wavelength, then detuning the signal and idler away from degeneracy will, to third order, leave the phase-mismatch (∆k) unchanged so that the tuning bandwidth near degeneracy will be wide.…”
mentioning
confidence: 98%
“…Extremely wide tuning bandwidths for parametric processes are associated with the zero-GVD wavelength [7]. For an interaction where d 2 k/dω 2 = 0 at the degenerate signal-idler wavelength, then detuning the signal and idler away from degeneracy will, to third order, leave the phase-mismatch (∆k) unchanged so that the tuning bandwidth near degeneracy will be wide.…”
mentioning
confidence: 99%